ALGUNOS ELEMENTOS DE LA FLORA TUPENSE (CARBONIFERO) EN LA CUENCA SAN RAFAEL, ARGENTINA (Ameghiniana, 2013)
In this paper the systematic study of a late Paleozic flora from El Imperial Formation (San Rafael Basin), is presented. The elements that compose this assemblage belong to the NBG Zone (Nothorhacopteris-Botrychiopsis-Ginkgophyllum Zone). The taphoflora is represented by the following laxa: Fedekurtzia argentina (Kurtz) Archangelsky, Botrychiopsis weissiana Kurtz emed. Archangelsky and Arrondo, Diplothmema bodenberi (Kurtz) Césari, Cordaites riojanus Archangelsky and Leguizamón, Cordaites sp., Paracalamites australis Rigby, Articulate A (Family Autophyllitaceae) and Form A (incertae sedis). The presence of these elements in San Rafael Basin, extends the geographical distribution of the NBG Zone during middle to late Carboniferous.